GE_GERICHTE A/4277/2020 vom 20. September 2021 - GE Cour de justice (2021)
LAPSUS CALAMI;ERREUR DE CALCUL;DEMANDE ADRESSÉE À L'AUTORITÉ;RÉVISION(DÉCISION) | LPFisc.58; LIFD.150; LPFisc.55.al1; LIFD.147.al1